UTILIZING TOURISM AND CULTURAL HERITAGE TO ADDRESS YOUTH UNEMPLOYMENT IN NORTH SUMATRA - Raja Sungai Simbolon; Steven Nikson Sitanggang; Dina Sri Elvina Hutabarat; Azura Hinayah; Meisuri (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
Youth unemployment is a growing concern in North Sumatra, exacerbated by a skills mismatch between the workforce and industry needs. Despite the region's rich cultural heritage and abundant natural resources, especially in tourism, these sectors remain underdeveloped. The purpose of this study is to explore how cultural and tourism industries can help alleviate youth unemployment in North Sumatra. Data was collected through surveys and a review of literature, highlighting a lack of vocational training in relevant areas, particularly in hospitality and cultural preservation. Results indicate that the tourism and cultural sectors have untapped potential for job creation. However, without targeted vocational training and collaboration between the government and private sector, this potential will remain unrealized. The discussion focuses on addressing the skills gap and integrating cultural heritage into tourism to create sustainable employment opportunities. In conclusion, strategic investment in vocational education, alongside the promotion of cultural tourism, can significantly reduce unemployment while preserving North Sumatra’s unique cultural identity.